Osteitis fibrosa cystica masquerading as bone neoplasm. (7th May 2018) - Garla, Vishnu Vardhan; Akhtar, Israh; Salim, Sohail; Subauste, Angela
Abstract : A 50-year-old female patient with no significant medical history presented with left knee pain. Radiographs of the knee showed a circumferential swelling of the distal femur suggestive of neoplasia. Further evaluation revealed multiple lesions in the left iliac bone and proximal femur. Biopsy was suggestive of a reparative granuloma or an aneurysmal bone cyst. Laboratory assessment showed hypercalcaemia and elevated parathyroid hormone consistent with severe primary hyperparathyroidism. Osseous survey was significant for salt and pepper appearance of the skull. Ultrasound of the neck and 99m Tc-sestamibi parathyroid scintigraphy localised a left parathyroid adenoma/carcinoma. Parathyroidectomy was successful, and a large parathyroid adenoma was excised. Six months later, the patient was doing fine with her gait returning to normal. On follow-up 2 years later, she had no recurrence of the lesions.